Penerapan metode full costing dalam menentukan harga pokok produksi pada Pabrik Tahu Langgeng Jaya - Rohadi, Erika Ambarwati; Pusung, Rudy J.; Latjandu, Lady Diana (Manajemen Bisnis dan Keuangan Korporat, 2025)
Accurate determination of the cost of goods manufactured (COGM) is essential for ensuring competitive pricing and sustainable profitability, particularly for micro and small enterprises that commonly rely on informal cost records. However, many small-scale food producers still calculate production costs based on estimates that exclude indirect and fixed cost components, resulting in understated product costs and suboptimal pricing decisions. This study aims to analyze the application of the full costing method in determining COGM at Langgeng Jaya Tofu Factory and to compare it with the conventional approach used by the business. Using a qualitative case study, data were collected through interviews, direct observations, and documentation of cost components. The results reveal that the full costing method provides a more comprehensive and accurate representation of production costs by incorporating auxiliary materials and asset depreciation, which were previously omitted. The total annual production cost amounted to IDR851,718,660 for 28,800 boards of tofu, yielding a COGM of Rp29,573 per board—higher than the company’s prior estimate of IDR26,020. These findings indicate that neglecting fixed and indirect costs leads to cost distortions and unrealistic pricing. This study contributes to the literature by demonstrating the applicability and practical relevance of full costing for small traditional food manufacturers and provides evidence-based recommendations to enhance cost management and pricing accuracy in micro and small enterprises.